2019
DOI: 10.14738/assrj.69.6176
|View full text |Cite
|
Sign up to set email alerts
|

Hegemonial Evaluation of Importance of Women Education and their Socio Economic Development in Fika Local Government Area , Yobe State, Nigeria

Abstract: The paper   discussed the importance of women education and the socio economic development in Fika local government area of Yobe state, Nigeria. The paper focused on the concept of women education, the concept of socio-economic development and the importance of women education in socio-economic development. This study employed quantitative approach with descriptive correlation design and also the total population of 66901 and the sample size of 382 respondents while questionnaire and interview guide were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Baba and Anumaka (2019) investigated the significance of women education on the socio economic development in Yobe state, Nigeria. The research revealed that women Education have a very significant and positive relationship with their household income level, standard of living, and economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baba and Anumaka (2019) investigated the significance of women education on the socio economic development in Yobe state, Nigeria. The research revealed that women Education have a very significant and positive relationship with their household income level, standard of living, and economic development.…”
Section: Literature Reviewmentioning
confidence: 99%